Reliability of the Hirschsprung-Associated Enterocolitis Score in Clinical Practice - Dore, Mariela; Vilanova Sanchez, Alejandra; Triana Junco, Paloma; Barrena, S.; De Ceano-Vivas, María; Jimenez Gomez, Javier; Andres Moreno, Ane M.; Lopez Santamaria, Manuel; Martinez, Leopoldo (European Journal of Pediatric Surgery, 2019)
Introduction There is a lack of an agreed Hirschsprung-associated enterocolitis (HAEC) definition. In 2009, a HAEC score was proposed for the diagnosis of HAEC episodes. Our aim was to apply the HAEC score on HAEC episodes to determine its diagnostic efficiency and whether it correlated to its severity.Methods Retrospective study of patients with HAEC admitted between 2000 and 2016. Episodes of HAEC were identified and the HAEC score was calculated. A cut-off of ≥ 10 according to Pastor et al and ≥ 4 according to Frykman et al were used. A Pearson's correlation coefficient was performed for outcome variable: length-of-stay (LOS).Results Note that 21/93 (22.6%) patients with Hirschsprung's disease presented 50 HAEC episodes with a median of 2 (1–5) episodes during an 8.3-year (2–15.6) follow-up. The most common symptoms were foul-smelling (86% [43/50]) and explosive (60% [30/50]) diarrhea. Physical findings showed a distended abdomen (76% [38/50]) and fever (60% [30/50]) with dilated bowel (82% [41/50]) and rectosigmoid cut-off (80% [40/50]) identified on X-rays. Only 34% (17/50) showed abnormal laboratory findings. Patients were admitted with a median LOS of 7 days (1–28). A HAEC score of 9 (2–16) was found, and only 50% (25/50) of patients met the initial criteria (score of 10 points). However, the use of a 4-point cut-off would have allowed the diagnosis of 98% (49/50) of the patients. A positive linear correlation was found for LOS and HAEC score (r = 0.3, p = 0.014).Conclusion There is no standardized definition for HAEC. The initial HAEC score cut-off is restrictive and might fail to identify milder episodes. The positive correlation with LOS and thus HAEC severity might aid in patient information and anticipation of treatment.
Keywords: Hirschsprung's disease; Hirschsprung-associated enterocolitis; Hirschsprung's complications; Hirschsprung-associated enterocolitis severity; Hirschsprung-associated enterocolitis score